2009
DOI: 10.1007/s11999-009-0924-5
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Heterotopic Ossification of the Hip: Systematic Review and Meta-Analysis

Abstract: Heterotopic ossification (HO) is a potentially severe, if infrequent, complication in hip surgery, and uncertainty exists regarding whether to use NSAIDs or radiation in its prevention. Thus, we systematically reviewed the literature in MedLine, EMBASE, CINAHL, and the Cochrane Controlled Trial Register and, after ruling out publication bias and data heterogeneity, performed a meta-analysis of randomized, controlled trials to assess effectiveness and complications of NSAIDs and radiation in the prevention of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 32 publications
1
62
1
3
Order By: Relevance
“…However, these studies have not evaluated patient populations treated in a uniform surgical fashion by one surgeon, and risk factors were not consistent among those studies. In this retrospective study, which evaluated a relatively homogeneous patient population, and which excluded a number of patients who were identified in advance as being at high risk (and so who received prophylaxis with indomethacin), we showed rates of HO comparable to previous studies [9,28,32] and we identified prolonged mechanical ventilation as a risk factor for the development of severe HO. Although we cannot recommend for or against routine prophylaxis, patients who are expected to be ventilated for a prolonged period may benefit from prophylaxis.…”
Section: Discussionsupporting
confidence: 65%
“…However, these studies have not evaluated patient populations treated in a uniform surgical fashion by one surgeon, and risk factors were not consistent among those studies. In this retrospective study, which evaluated a relatively homogeneous patient population, and which excluded a number of patients who were identified in advance as being at high risk (and so who received prophylaxis with indomethacin), we showed rates of HO comparable to previous studies [9,28,32] and we identified prolonged mechanical ventilation as a risk factor for the development of severe HO. Although we cannot recommend for or against routine prophylaxis, patients who are expected to be ventilated for a prolonged period may benefit from prophylaxis.…”
Section: Discussionsupporting
confidence: 65%
“…These medications did not appear effective in the present case histories, although they may have inhibited further development of HO. Nonsteroidal anti-inflammatory agents and radiation are known to be effective prophylaxis against HO following hip surgery in civilians [24]. A program description of the Walter Reed Amputee Patient Care Program indicates physicians prescribed nonsteroidal anti-inflammatory drugs such as Celebrex for combat amputees, unless contraindicated, for both prophylaxis and treatment of HO [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another option is radiation treatment, which can be used for both therapeutic and prophylactic purposes in HO (4)(5)(6). The therapeutic use of radiation therapy in established HO was first described by Schaeffer and Sosner (5) in 1995, who found that giving a 2 gray dose of radiation for several consecutive days resulted in improved range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was successfully treated with oral bisphosphonate and aggressive physiotherapy. drug such as indomethacin (6). It is generally recommended to initiate anti-inflammatory drug therapy within one day of surgery and to continue for a minimum of three weeks (8).…”
Section: Discussionmentioning
confidence: 99%